Stable zigzag edges of transition-metal dichalcogenides with high catalytic activity for oxygen reduction. (1st April 2020) - Hao, Yu; Xu, Li-Chun; Pu, Jibin; Wang, Liping; Huang, Liang-Feng
Abstract: Developing non-precious and efficient oxygen reduction reaction (ORR) catalysts to replace Pt-based materials is of vital importance for hydrogen fuel cells. Transition-metal dichalcogenides (TMD) are a typical group of catalysts that have been previously applied for hydrogen-evolution and hydrodesulfurization reactions. Using density-functional-theory calculations, we explore the prospect of both traditional and Janus TMDs as electrochemical ORR catalysts by studying their planar surfaces and different kinds of edges. Among the tens of surfaces, armchair edges, and zigzag edges of Mo- and W-based systems screened here, we find that both excellent stability and high catalytic activity can be simultaneously achieved for the zigzag edges of WSe2 and WSSe. The overpotentials of different zigzag edges of WSe2 and WSSe vary between 0.43 and 0.64 V, as low as that of the prototypical Pt electrode ( ∼ 0.45 V). The comprehensive ORR activities of TMD-based surfaces and edges studied here, as well as the high ORR activity discovered for specific zigzag edges, can not only be readily validated by experiments but also facilitate their future related applications by providing a complete structure–property relationship. Those low overpotentials are benefited from the moderate OH–edge bonding strength, and the revealed microscopic electornic-structure mechanisms here will also be useful for further optimizing the ORR activities of TMD edges through, e.g., chemical, mechanical, and potentiostatic approaches.